Diversity, Disturbance and Regeneration Status of forests along an Altitudinal Gradient in Paddar Valley, Northwest Himalayas - Kumar, Suresh; Sharma, Sanjay (Indian Forester, 2014)
The present study deals with the phytosociological analysis, anthropogenic impacts and regeneration status of tree species in five dominant forest types along an altitudinal gradient in Paddar valley of Northwest Himalaya. The tree density varied between 179 to 245 trees/ha whereas the total basal area varied between 24.7 and 37.7 mÂ²/ha in five forest types. The value of Shannon-Weiner index (H') was found maximum for western mixed coniferous forest (1.75) whereas Concentration of dominance (Cd) and Evenness (J') were found maximum for dry temperate deciduous forest (0.41) and dry deodar forest (0.32) respectively. The maximum disturbance was found in the dry temperate deciduous forests due to heavy dependence of the locals on oak, Quercus baloot for fuelwood and fodder. The results pertaining to regeneration status of 18 tree species shows 4 species with good regeneration,6 species with fair regeneration and 5 species with poor regeneration status whereas 3 tree species were found to have no regeneration at all. The regeneration was good for mixed coniferous forest and birch fir forests, poor for broadleaved and coniferous forest and fair for dry temperate deciduous forest and dry deodar forests.